2020
DOI: 10.1002/cbic.202000027
|View full text |Cite
|
Sign up to set email alerts
|

Cofactors as Molecular Fossils To Trace the Origin and Evolution of Proteins

Abstract: Due to their early origin and extreme conservation, cofactors are valuable molecular fossils for tracing the origin and evolution of proteins. First, as the order of protein folds binding with cofactors roughly coincides with protein-fold chronology, cofactors are considered to have facilitated the origin of primitive proteins by selecting them from pools of random amino acid sequences. Second, in the subsequent evolution of proteins, cofactors still played an important role. More interestingly , as metallic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 114 publications
(309 reference statements)
0
27
0
Order By: Relevance
“…Several cofactors (NAD(P), FAD and coenzyme A) contain AMP as a structural element which is not involved in catalysis but rather serves as a ‘handle’ for binding to enzymes [174]. Nucleotide-containing cofactors together with inorganic cofactors represent two main groups of cofactors that are assumed to be of prebiotic origin and played the primary role in protein evolution [42]. While metal ions and minerals that resemble metal ion clusters found in the modern proteins (such as Fe/S clusters) should have been widespread in the primordial Earth environment, nucleotide-containing cofactors' provenance in the peptide-polynucleotide stage provides a direct testament to how these two types of molecule types coevolved intimately during early chemical evolution [175177].…”
Section: Evolutionary Significance Of Cofactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cofactors (NAD(P), FAD and coenzyme A) contain AMP as a structural element which is not involved in catalysis but rather serves as a ‘handle’ for binding to enzymes [174]. Nucleotide-containing cofactors together with inorganic cofactors represent two main groups of cofactors that are assumed to be of prebiotic origin and played the primary role in protein evolution [42]. While metal ions and minerals that resemble metal ion clusters found in the modern proteins (such as Fe/S clusters) should have been widespread in the primordial Earth environment, nucleotide-containing cofactors' provenance in the peptide-polynucleotide stage provides a direct testament to how these two types of molecule types coevolved intimately during early chemical evolution [175177].…”
Section: Evolutionary Significance Of Cofactorsmentioning
confidence: 99%
“…Though requires phosphorylated monomers and many branching reactions possible given the various nucleophilic moieties on nucleotides [18,3537]functional (catalytic) capacitydiverse. Could have supported early metabolism [38,39]limited primarily to phosphoryl group transfer chemistry (with the important exception of the ribosome, which catalyses aminolysis of esters) [38]cofactor utilization4diverse [4042]limited primarily to Mg 2+ [4346]tolerance to backbone impuritysubstitution of amides for esters associated with incremental decreases in stability [13,47,48]base-pairing possible with diverse backbones (peptides, other sugars [49]), though typically tertiary structures not compatible [50]pH tolerancehigh—stable between 3 and 10low—stable between 5 and 7—due to both backbone cleavage and depurinationtolerance to high Fe 2+ levels (and other divalent cations)high [43,5153]low—catalyses hydrolysis of phosphodiesters through ‘in-line’ and Fenton mechanisms [45,46]unassisted refoldability5generally, yes. Complex proteins may require chaperones or translation, but simple proteins can fold unassisted [54,55]generally, no.…”
Section: Introductionmentioning
confidence: 99%
“…We constructed such a reaction: ribose 5phosphate + 2 glucose 6-phosphate => PRPP + 2 glucose. Under the substance concentration condition used in the network expansion simulation, this reaction is thermodynamically favorable even at −25 °C (with a free energy of −33.56 kJ/mol), implying that glucose- Nucleotides are the basic components of RNA and constitute the cofactors of many proteins, so they are of great significance in the origin of life [31]. As there is no phosphorus in the thioester-dependent networks, it is obviously impossible for them to synthesize nucleotides (Figure 2B and Figure S1B).…”
Section: Resultsmentioning
confidence: 99%
“…Nucleotides are the basic components of RNA and constitute the cofactors of many proteins, so they are of great significance in the origin of life [ 31 ]. As there is no phosphorus in the thioester-dependent networks, it is obviously impossible for them to synthesize nucleotides ( Figure 2 B and Figure S1B ).…”
Section: Resultsmentioning
confidence: 99%
“…Already in the 70s Harold White pointed out that nucleotide coenzymes play a major role in contemporary metabolism 3,4 . Since then, it has been widely suggested that coenzymes may be the fossils of a nucleotide-based ancient metabolism prior to the emergence of the first proteins 2,5 . In fact, in the beginning of the 80s, the first examples of ribozymes were discovered, strongly supporting White’s hypothesis 6,7 .…”
Section: Introductionmentioning
confidence: 99%